Penatalaksanaan Perawatan Perineal dengan Daun Sirih dengan Masalah Risiko Infeksi pada Luka Perineum Ibu Nifas di Desa Kepuh - Ayu Wulandari; Tutik Rahayuningsih (Indonesian Journal on Medical Science, 2022)
Postpartum is the period after the expulsion of the placenta until the reproductive organs recover, the postpartum period lasts for 40 days. Problems that occur after delivery are puerperal infections that occur due to injury to the birth canal. To avoid perineal infection, it is necessary to treat the perineum by using boiled betel leaf (Piper Betle Linn). This study aims to describe the management of perineal care with betel leaf with the problem of risk of infection in the perineal wound of postpartum mothers. Qualitative descriptive research design using a case study (Case Study Research) with a nursing process approach. The technique of taking the subject is non-probability sampling with a purposive sampling approach. Assessment data there are sutures on the perineum, REEDA; there is redness, there is swelling, there are no bleeding spots, there is no excretion, the union of the wound is not good. The suture wound was still wet, there was lochia rubra, odorless lochia, dirty perineum, dirty vulva. Nursing diagnosis risk of infection related to tissue trauma. Nursing actions performed perineal care with vulvar hygiene with betel leaf for seven days, morning and evening for 20 minutes. General evaluation of perineal care with betel leaf can be effective in overcoming the risk of infection in perineal wounds. Perineal treatment with betel leaf can overcome the risk of infection in perineal wounds.